Optimal design of a single-phase APF based on PQ theory - Dur Muhammad Soomro; Sager K. Alswed; Mohd Noor Abdullah; Nur Hanis Mohammad Radzi; Mazhar Hussain Baloch (Institute of Advanced Engineering and Science, 2020)
The instantaneous active and reactive power (PQ) theory is one of the most widely used control theory for shunt active power filter (SAPF), which can be implemented in single-phase and three-phase systems. However, the SAPF with PQ theory still had ability to improve to become more efficient. This paper presents the optimal design of a single-phase SAPF in terms of reducing the current harmonic distortion and power loss in voltage source inverter (VSI) controlled with the semiconductor switching devices IGBT, MOSFET and Hybrid (combination of IGBT and MOSFET). In order to reduce the switching frequency and power loss of VSI, instead of using single-band hysteresis current controller (HCC), double-band HCC (DHCC) and triple-band HCC (THCC) is used in the SAPF. The designed SAPF is tested with different non-linear loads to verify the results by using MATLAB Simulink.